Group conflict handling under moderate evaluative partial mediation using entropic decision framework. (28th June 2022) - Anjaria, Kushal
Abstract: The present paper aims to present entropy and fuzzy degrees of the truth‐based framework to handle the group conflict under moderate evaluative, partial mediation. For group conflict handling, the present work considers Thomas and Kilmann's five conflict‐handling modes: competing, collaborating, avoiding, accommodating, and compromising. A methodology proposed in the current work systemically formalizes decision‐making on deploying a conflict‐handling method with mediators' opinions. The formalization of decision‐making elucidated in the present work involves measurements based on entropy and fuzzy degrees of truth. The current work applies the developed formal quantitative framework to a well‐known case of group conflict that involves conflict among a group of engineering students. The case supports the proposed formal framework. Behavioral, psychological, and cognitive facts about engineers come in handy for validation of the proposed framework. The case shows that the proposed approach can be highly generalized, interpretable, and replicable.